2017
DOI: 10.1136/annrheumdis-2017-211574
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise dose increase of febuxostat is comparable with colchicine prophylaxis for the prevention of gout flares during the initial phase of urate-lowering therapy: results from FORTUNE-1, a prospective, multicentre randomised study

Abstract: ObjectivesTo determine whether febuxostat with stepwise dose increase is as useful as colchicine prophylaxis in reducing gout flares during the initial introduction of urate-lowering therapy in patients with gout in comparison with febuxostat with no dose titration.MethodsIn this prospective, multicentre, randomised open-label comparative study, patients were randomised to group A (stepwise dose increase of febuxostat from 10 to 40 mg/day), group B (fixed-dose febuxostat 40 mg/day plus colchicine 0.5 mg/day) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 36 publications
1
78
0
3
Order By: Relevance
“…The validation parameters were robust and reproducible, including the ISR, which confirmed the performance of the bioanalytical method. We believe that the simultaneous assay can be readily adopted for analysis of the two drugs in human plasma since it has been shown that a fixed dose combination of colchicine and febuxostat has therapeutic benefits in treating gout patients (Yamanaka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation parameters were robust and reproducible, including the ISR, which confirmed the performance of the bioanalytical method. We believe that the simultaneous assay can be readily adopted for analysis of the two drugs in human plasma since it has been shown that a fixed dose combination of colchicine and febuxostat has therapeutic benefits in treating gout patients (Yamanaka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many strategies have been developed and are currently being used in the management of gout with the ultimate aim of optimizing the therapy, balancing the risk of side effects associated with pharmacological intervention with the established benefits the therapy provides in disease management (Ragab, Elshahaly, & Bardin, 2017; Soskind, Abazia, & Bridgeman, 2017). The recent work of Yamanaka et al (2018) has suggested the utility of a combination option of febuxostat (a xanthine oxidase inhibitor; Figure 1) and colchicine (a well‐established anti‐gout drug; Figure 1) for the effective management of gout flares. In this study involving gout patients, the data unequivocally suggested that low‐dose colchicine prophylaxis along with a step‐wise dose increase of febuxostat reduced gout flares compared with a group of patients that received a fixed dose of febuxostat as a standalone therapy (Yamanaka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a non-competitive xanthine oxidase inhibitor (XOI), Febuxostat appears to be superior over the competitive XOI allopurinol, owing to its greater potency, specificity and a decreased reliance on renal excretion. It has been shown to be better than fixed-dose (300 mg) allopurinol in terms of its efficacy as a urate-lowering agent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is well established that febuxostat leads to a quicker drop in the level of serum urate compared with allopurinol. A recent Japanese randomized controlled trial (RCT) showed that stepwise dosing (10 mg, 20 mg, and 40 mg) of febuxostat can reduce flares from 36% to 20.8%, compared with a fixed dose of 40 mg . Therefore, it would be valid to investigate whether stepwise dosing of febuxostat starting at 10 mg or 20 mg may relieve cardiovascular (CV) side effects and flares.…”
mentioning
confidence: 99%